Directed Gap Closure in Large-Scale Sequencing Projects - Frohme, Marcus; Camargo, Anamaria A.; Czink, Claudia; Matsukuma, Adriana Y.; Simpson, Andrew J.G.; Hoheisel, Jörg D.; Verjovski-Almeida, Sergio

(untitled) (Genome Research, 2001)
A problem in many sequencing projects is the final closure of gaps left in the clone libraries, which serve as templates for sequencing, because of uncloned or unclonable genomic areas. By use of theXylella fastidiosa genome as a test system, we present here an approach to generate, in a directed manner, sequence information from those gaps. We suggest using the complete clone library as a competitor against the genomic DNA of interest in a subtractive hybridization procedure similar to representational difference analysis (RDA). The resulting sequence information can be used to screen selectively other clone resources or serve directly for gap closure.